PENGARUH PILATES EXERCISE DAN WILLIAM’S FLEXION EXERCISE TERHADAP NYERI MENSTRUASI KARENA DYSMENORRHEA PRIMER PADA REMAJA - Wahyuningrum, Andini; Hariandja, Andy Martahan Andreas; Trioclarise, Rovika (Jurnal Fisioterapi dan Kesehatan Indonesia, 2025)
Background: Dysmenorrhea is muscle cramps during menstruation, this is the most common problem experienced by women with menstrual disorders. Purpose: to determine the effect of Pilates Exercise and William's Flexion Exercise on menstrual pain due to primary dysmenorrhea in adolescents. Methods: This study used a quasi-experimental study with a pre-test - post-test two group design. The population consisted of all class XI students at SMA N 104 Jakarta and a sample of 30 people, 15 people with Pilates Exercise intervention, and 15 people with William's Flexion Exercise intervention based on predetermined inclusive criteria. The intervention was carried out for 3 weeks with a frequency of 3 times a week, as well as a pain measurement tool using the Numerical Pain Rating Scale (NPRS). Results: The Paired Sample T-Test obtained p=0.000 in the Pilates Exercise group, while p=0.109 in the William's Flexion Exercise group. The Independent T-Test obtained p=0.001, which means that there was a significant difference between the two interventions. Conclusion: The Pilates Exercise method is better than William's Flexion Exercise in reducing menstrual pain due to primary dysmenorrhea in adolescents.